Short-term high salt intake impairs hepatic mitochondrial bioenergetics and biosynthesis in SIRT3 knockout mice. (3rd April 2019) - Jiang, Lihan; Chen, Qinghua; Wu, Meiling; Ji, Tingting; Liu, Shanlin; Zhu, Fengge; Shi, Dongyun
Abstract: High salt intake (HS) is an important factor in the development of many metabolic diseases. The liver is the metabolic center in the body. However, the effect of short-term HS on the liver mitochondria and its mechanism are still unclear. In this study, we investigated the effects of short-term HS on liver mitochondrial function. We found that HS reduced Sirtuin3 (SIRT3) protein level, increasing protein carbonylation in mice liver. HS intake decreased ATP production, mitochondrial transcription factor A (TFAM), and complex I level. SIRT3 knockout (SKO) mice exhibited similar results with HS-treated wild-type mice but with a less extent of carbonylation and ATP reduction. Our study shows that short-term HS led to increased hepatic oxidative state, impaired mitochondrial biosynthesis, and bioenergetics. HS-treated mice could still maintain hepatic glucose homeostasis by compensatory activation of Adenosine 5′-monophosphate-activated protein kinase (AMPK). However, in HS-treated SKO mice, AMPK was not activated, instead, the glycogen synthase activity increased, which caused an exceptionally increased glycogen accumulation. This study provides evidence that short-term HS intake could cause the early hepatic metabolic changes, highlighting the importance of controlling salt intake especially in those patients with defects in SIRT3. Highlights: High salt intake down-regulates SIRT3 protein level and increases oxidation. High salt intake activates AMPK via AMP-dependent pathway. High salt intake impairs energy metabolism. High salt combined with SIRT3 knockout results in glycogen accumulation.